Teaching English Grammar According To Primary School Children Age`S (Texas Journal of Philology, Culture and History, 2025)
This article is discussing about teaching English grammar to primary school children. Teaching foreign languages to children in primary school seems to be an urgent issue of modern teaching methods. Psychologists have proven that children who start learning a foreign language at the age of 8-9 achieve results much higher than children who start learning it at the age of 12. The need to know the Uzbek language as the state language, the Russian language as the language of international communication, and the English language was placed among the important tasks of the state.